Real life results of direct acting antiviral therapy for HCV infection in HIV–HCV-coinfected patients: Epi-Ter2 study. Issue 6 (2nd June 2020) - Piekarska, A.; Jabłonowska, E.; Garlicki, A.; Sitko, M.; Mazur, W.; Jaroszewicz, J.; Czauz-Andrzejuk, A.; Buczyńska, I.; Simon, K.; Lorenc, B.; Dybowska, D.; Halota, W.; et al.
ABSTRACT: The aim of this study was to evaluate the baseline demographics and real-life efficacy of direct acting antivirals (DAAs) in HIV–HCV-positive patients as compared to patients with HCV monoinfection. The analysis included 5690 subjects who were treated with DAAs: 5533 were HCV-positive and 157 were HIV–HCV-positive. Patients with HCV-monoinfection were older ( p  < .0001) and in HIV–HCV group there were more men ( p  < .0001). Prevalence of genotype 1a ( p  = .002), as well as of genotypes 3 and 4 ( p  < .0001) was higher in HIV–HCV-coinfected patients. Genotype 1b was more frequent ( p  < .0001) in the HCV-mono-infection group. Patients with HCV-monoinfection had a higher proportion of fibrosis F4 ( p  = .0004) and lower proportion of fibrosis F2 ( p  < .0001). HIV–HCV-coinfected individuals were more often treatment-naïve ( p  < .0001). Rates of sustained viral response after 12 weeks did not differ significantly between both groups (95.9% versus 97.3% in coinfection and monoinfection group, respectively; p > .05). They were, however, influenced by HCV genotype ( p  < .0001), stage of hepatic fibrosis ( p  < .0001), male sex ( p  < .0001), BMI ( p  = .0001) and treatment regimen modifications ( p  < .0001). Although factors associated with worse response to therapy (male sex, genotype 3) occurred more often in the HIV coinfection group, real-life results of DAAs did not differ significantly between both populations.